MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI BILANGAN BERPANGKAT DAN BENTUK AKAR DENGAN PEMBERIAN TUGAS TERSTRUKTUR TERHADAP SISWA KELAS IX - ilham ilham (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
This research is a classroom action research which aims to improve mathematics learning outcomes on the material of numbers with exponents and root forms through the application of structured assignments. The subjects of this study were grade IX students of SMPN 5 Mallusetasi in the Even Semester of the 2019/2020 Academic Year.This research was conducted in two cycles, where in cycle 1 it was conducted with three face-to-face meetings and in one meeting the learning outcomes test was conducted and in cycle 2 consisted of four meetings and one meeting the learning outcomes test was conducted. The research data is sourced from the learning outcomes test 1 and learning outcomes test 2.Based on the results of the study, it can be concluded that the mathematics learning outcomes of class IX students of SMPN 5 Mallusetasi have increased from cycle 1 to cycle 2 after learning by giving structured assignments. The average mathematics learning outcomes of students in the first cycle of 80.2 increased to 84.4 in the second cycle. Classical completeness in the second cycle reached 93%. So it can be concluded that mathematics learning outcomes increase with the method of giving structured assignments.Â